The English Teacher Readiness in Implementing The Emancipatory Curriculum at A Private School in Indonesia - Dienha Habibie; Hanna Sundari (Journal of English Language Learning, 2024)
This study investigates the readiness of English teachers in implementing the Emancipatory Curriculum at SMK Perjuangan Bangsa Ligung, Majalengka, by highlighting the importance of teacher readiness in educational reform. Using a qualitative case study methodology, data were collected through structured interviews, classroom observations, and document analysis involving four English teachers at the school where the study was conducted. The results showed varying levels of readiness among teachers, with some effectively using active and participatory learning models, while others faced challenges in creating an interactive classroom environment. Factors such as adequate training and technological support have a positive effect on readiness, while resource and time constraints pose significant challenges. The discussion emphasized the need for continuous professional development and institutional support to improve teachers' abilities and ensure successful curriculum implementation, ultimately contributing to improved student engagement and learning outcomes Keyword: Teacher Readiness, Emancipatory Curriculum, Learning Models, Educational Challenges